2018
DOI: 10.3389/fnint.2018.00048
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Memory Comparison Between Tinnitus and Normal Cases Using Event-Related Potentials

Abstract: About 20 percent of people above 60 years old suffer from tinnitus though no definitive treatment has been found for it. Evaluation of electrical brain activity using Event-Related Potentials (ERPs) is one of the methods to investigate the underlying reasons of tinnitus perception. Previous studies using ERPs suggest that the precognitive memory in tinnitus groups is negatively affected in comparison to the normal hearing groups. In this study, cognitive memory has been assessed using visual and auditory P300 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 16 publications
1
9
0
2
Order By: Relevance
“…Previous MMN and equivalent studies (Weisz et al, 2004;Holdefer et al, 2013;Mahmoudian et al, 2013;Asadpour et al, 2018;El-Minawi et al, 2018;Mohebbi et al, 2019b) have varied according to the type of deviant, the paradigm used, control matching for hearing loss, and, importantly, whether stimulus frequencies were standardized or targeted to subjects' tinnitus. Studies with nontargeted stimulus frequencies have reported slightly smaller MMN responses to deviants of all types tested (Holdefer et al, 2013;Mahmoudian et al, 2013), and minor differences in P300 oddball responses to auditory and visual stimuli (Asadpour et al, 2018). At the audiometric (not tinnitus) edge frequency, tinnitus patients showed larger MMN responses (in the N1 timeframe) to downward frequency deviants than hearing unmatched controls (Weisz et al, 2004), and unchanged responses one octave lower.…”
Section: Previous Mmn Studies In Tinnitusmentioning
confidence: 99%
“…Previous MMN and equivalent studies (Weisz et al, 2004;Holdefer et al, 2013;Mahmoudian et al, 2013;Asadpour et al, 2018;El-Minawi et al, 2018;Mohebbi et al, 2019b) have varied according to the type of deviant, the paradigm used, control matching for hearing loss, and, importantly, whether stimulus frequencies were standardized or targeted to subjects' tinnitus. Studies with nontargeted stimulus frequencies have reported slightly smaller MMN responses to deviants of all types tested (Holdefer et al, 2013;Mahmoudian et al, 2013), and minor differences in P300 oddball responses to auditory and visual stimuli (Asadpour et al, 2018). At the audiometric (not tinnitus) edge frequency, tinnitus patients showed larger MMN responses (in the N1 timeframe) to downward frequency deviants than hearing unmatched controls (Weisz et al, 2004), and unchanged responses one octave lower.…”
Section: Previous Mmn Studies In Tinnitusmentioning
confidence: 99%
“…Concerning P2, reduced amplitudes [ 89 ] and higher latencies [ 93 , 98 ] have been found in tinnitus patients in several studies. Increased latency of P3 without amplitude change was found in tinnitus patients in the majority of studies [ 73 , 93 , 99 ], while other studies found that the amplitude of P3 in tinnitus patients was significantly lower than in controls and there is no difference in latency [ 89 , 91 , 92 , 100 , 101 ]. Furthermore, larger P3 amplitudes along with prolonged latency were observed in individuals with tinnitus [ 96 ].…”
Section: Electrophysiological Methodsmentioning
confidence: 99%
“…P3 is reported to be altered in individuals with tinnitus, which indicates attentional dysfunction. 20 21 22 23 24 25…”
Section: Introductionmentioning
confidence: 99%
“…There have been shreds of evidence that tinnitus affects either or both the sensory and cognitive components of CAEPs, suggesting a difference in the way sound is being processed. 20 21 22 23 24 25 26 27 28 In vitro animal studies 16 have shown that the hyperactive neural firings decrease as a result of RIT. However, there are no neurophysiological studies reported on humans following RIT or educational counselling.…”
Section: Introductionmentioning
confidence: 99%